Peripheral blood TIM-3 positive NK and CD8+ T cells throughout pregnancy: TIM-3/galectin-9 interaction and its possible role during pregnancy. - Matyas Meggyes; Eva Miko; Beata Polgar; Barbara Bogar; Balint Farkas; Zsolt Illes; Laszlo Szereday (PLoS ONE, 2014)
The T-cell immunoglobulin and mucin domain (TIM) family is a relatively newly described group of molecules with a conserved structure and important immunological functions. Identification of Galectin-9 as a ligand for TIM-3 has established the Galectin-9/TIM-3 pathway as an important negative regulator of Th1 immunity and tolerance induction. Data about the TIM-3/Gal-9 pathway in the pathogenesis of human diseases is emerging, but their possible role during human pregnancy is not precisely known. The aim of our study was to investigate the number, phenotype and functional activity of TIM-3+ peripheral blood mononuclear cells during healthy human pregnancy.57 healthy pregnant women [first trimester (n = 16); second trimester (n = 19); third trimester (n = 22)] and 30 non-pregnant controls were enrolled in the study. We measured the surface expression of TIM-3 by cytotoxic T cells, NK cells and NK cell subsets as well as Galectin-9 expression by regulatory T cells by flow cytometry. We analyzed the cytokine production and cytotoxicity of TIM3+ and TIM3- CD8 T and NK cells obtained from non-pregnant and healthy pregnant women at different stages of pregnancy by flow cytometry. Serum Galectin-9 levels were measured by ELISA.Our results show that the numbers of peripheral NK and cytotoxic T cells and their TIM-3 expression do not change between the first, second and third trimesters of pregnancy. Compared to non-pregnant individuals, regulatory T cells show higher level of Galectin-9 expression as pregnancy proceeds, which is in line with the level of Galectin-9 in the patients sera. Cytotoxic T cells, NK cells and NK cell subsets expressing TIM-3 molecule show altered cytokine production and cytotoxicity during pregnancy compared to non-pregnant individuals.Our results indicate that Galectin-9 expressing regulatory T cells, TIM-3+ cytotoxic T cells and NK cells could play an important role in the maintenance of healthy pregnancy.